Gtavfifa
Rozwiązane

Przekształć wyrażenia do postaci sumy algebraicznej. Jeśli to możliwe zredukuj wyrazy podobne.



A) 3(x + 2y – 6) = 3x + 6x - 18



B) -2(4 – 3s + 5t) = -8 –3s +



C) x(2y – 5w + 54) =



D) 4(3 – 2x) + 5(3x + 6) =



E) 3a(b – 5) - 2b(3a – 5) = - 3ab – 15a + 10b



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

A) 3(x + 2y – 6) = 3x+6y-18

B) -2(4 – 3s + 5t) = -8+ 6s-10t

C) x(2y – 5w + 54) = 2xy-5wx+54x

D) 4(3 – 2x) + 5(3x + 6) =12-8x+15x+30=7x+42

E) 3a(b – 5) - 2b(3a – 5) =3ab-15a-6ab+10b= -3ab-15a+10b